BUDAYA ORGANISASI, ORIENTASI ETIKA DAN KINERJA KEUANGAN KOPERASI - Ratnadi, Ni Made Dwi; Asmara Putra, I Nyoman Wijana; Wirawati, Ni Gusti Putu (Jurnal Ekonomi dan Pariwisata, 2017)
ABSTRACT The aim of research to examine the influence of organizational culture and ethical orientation on the Cooperative’s financial performance. The study was conducted on cooperative members Cooperative Center (Puskop) Bali. Total population there were 36 cooperatives. The sampling method is nonprobability sampling with saturated or census sampling technique. Respondents are managers, the Management and Supervisory cooperative obtained 72 respondents. Primary and secondary data analyzed by Partial Least Square (PLS). The analysis showed that organizational culture positive effect on the financial performance of cooperatives. Ethical orientation positive effect on the financial performance of cooperatives. But the ethical orientation correlates with financial performance is smaller than the culture of the organization. Basically, the organization is a multicultural, therefore, needs the participation of human resources that provides value to the organization. Personal ethics and business ethics are inseparable and complementary presence in influencing the behavior of executives / managers or supervisors cooperative internalized into organizational behavior and corporate culture. Keywords: Organizational Culture, Orientation Ethics, Cooperative Financial Performance ABSTRAK Tujuan penelitian untuk menguji pengaruh budaya organisasi dan orientasi etika pada kinerja keuangan Koperasi. Penelitian dilakukan pada koperasi anggota Pusat Koperasi (Puskop) Bali. Jumlah populasi yang ada sebanyak 36 koperasi. Metode penentuan sampel adalah nonprobability sampling dengan teknik sampling jenuh atau sensus. Responden penelitian ini adalah Manajer, Pengurus dan Pengawas koperasi diperoleh 72 orang responden. Data primer dan sekunder dianalisis dengan Partial Least Square (PLS). Hasil analisis menunjukkan bahwa budaya organisasi berpengaruh pada positif pada kinerja keuangan koperasi. Orientasi etika berpengaruh positif pada kinerja keuangan koperasi. Akan tetapi orientasi etika memiliki korelasi dengan kinerja keuangan lebih kecil dibandingkan dengan budaya organisasi. Pada dasarnya organisasi merupakan multikultur, oleh karena itu diperlukan partisipasi sumber daya manusia yang memberi nilai pada organisasi. Etika personal dan etika bisnis merupakan kesatuan yang tidak terpisahkan dan keberadaannya saling melengkapi dalam memengaruhi perilaku pengurus/manajer atau pengawas koperasi yang terinternalisasi menjadi perilaku organisasi dan budaya perusahaan. Kata kunci: Budaya Organisasi, Orientasi Etika, Kinerja Keuangan Koperasi